Recent advances in the synthesis of hierarchically porous silica materials on the basis of porous glasses. (6th April 2016) - Inayat, Alexandra; Reinhardt, Björn; Herwig, Jan; Küster, Christian; Uhlig, Hans; Krenkel, Sharon; Raedlein, Edda; Enke, Dirk
Abstract : The methods for integrating an additional pore system in glass-based monoliths are reviewed with an emphasis on sintering and pseudomorphic transformation routes. Abstract : The thermal phase separation and subsequent leaching of sodium borosilicate glasses is a well established route for the preparation of porous glasses exhibiting adjustable pore sizes in the range of 1 nm up to almost 1 μm as well as a very flexible geometric shape. The combination of this route with a large spectrum of synthesis strategies for the implementation of an additional pore system enables the preparation of hierarchically porous glass-based materials. This review covers a wide range of preparative routes for hierarchically porous silica materials starting from the sodium borosilicate glass with a special emphasis on the very recent developments in this versatile field of materials engineering.